TEKNOLOGI BAHAN BANGUNAN RUMAH MURAH BERGAYA TRADISIONAL BALI (Bercermin pada Teknologi Bahan Bangunan SCHDS di UNIKA Soegijapranata) - Agung Diasana Putra, I Dewa Gede (Jurnal Natah; Vol. 1, No. 1 Februari 2003, 2012)
The house that expresses Traditional Balinese Building, is still interested and kept up by Balinese community, and this is also supported by local policy regarding to the utilize of Balinese Traditional Building. However, the ability of community to realize it is enormously limited related to the economic aptitude. It seems that it is crucial to create a building material that offer a strongly traditional impressed without ought to spend the high cost and simply processing. In Bali, the efforts to produce it, has already exist for instance the use of wall covered by using soil refined. That method that is employed by community, will be valuable if we combine with the new technology for example the brick traditionally technology combined with Habiteck Park will result the Balinese traditionally building material with low cost and simply processing. The result of this paper require to be pursued by intensely research to obtain a linked brick that be intended both intern of composition material and the various and precisely forms, thus this could be useful and present a high economic value in keeping up the effort to facilitate the house that that be able to fulfilled for Balinese community need without leave the Balinese Traditional Architecture Style.
Keywords: a linked brick, Balinese traditional.